Does radiation exposure during pediatric supracondylar humeral fracture surgery change according to the C-arm position? A comparison of two different techniques - (:unkn) unknown (My University, 2023)
Introduction: In the surgical treatment of supracondylar humeral fractures (SHF), the surgeon has to stand right next to the fluoroscopy device, so it is very important to know how to use it in the most appropriate way to reduce radiation exposure. The aim of this study was to investigate the effect of using C-arm in uniplanar (inverted) and biplanar (standard-horizontal) configurations on (1) the radiation exposure to the surgeon, and (2) surgical time and fluoroscopy exposure time. Material and methods: This prospective randomised study was conducted on 20 patients who underwent fluoroscopy during closed reduction and percutaneous pinning for a SHF. In the first configuration, the C-arm was inverted and the image intensifier was used as a surgical table. In the second configuration, the C-arm was used biplanar. The operations were performed by 5 surgeons, with each surgeon using each method only twice. During the operation, to find a value closed to direct radiation exposure measurement was made by attaching a dosimeter to the wrist and scatter radiation exposure was measured by attaching a dosimeter to the neck and waist of the surgeons. The operation time and fluoroscopy exposure time were determined. Results: The duration of operations performed with the biplanar C-arm position and the fluoroscopy exposure time in operations performed with the uniplanar method were found to be statistically significantly longer (p = 0.001). The measurements on the dosimeter worn on the neck of surgeons were found to be statistically significantly higher while using the uniplanar C-arm configuration (p = 0.001). There was no statistically significant difference between the dosimeter measurements on the wrists and waists of the surgeons and the C-arm configurations (p = 0.820; p = 0.185). Conclusions: Although the use of biplanar C-arm has no effect on radiation exposure to the surgeon\"s wrist, the most important advantages are that the neck area is exposed to less radiation and it shortens the fluoroscopy time so the use of a biplanar C-arm can be recommended. Level of evidence: Level II
Keywords: Tıp; Cerrahi Tıp Bilimleri; Acil Tıp; Ortopedi ve Travmatoloji; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Emergency Medicine; Orthopedics and Traumatology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ACİL TIP; ORTOPEDİ; Clinical Medicine (MED); CLINICAL MEDICINE; EMERGENCY MEDICINE; ORTHOPEDICS; Ortopedi ve Spor Hekimliği; Orthopedics and Sports Medicine; C-arm; Fluoroscopy position; Radiation exposure; Supracondylar humerus fracture